Menelusuri Potret Kehidupan Warga Desa Hargosari Kecamatan Tanjungsari Kabupaten Gunung Kidul - Maryatmo, Rogatianus (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Community Service Program is compulsory activity for students pursuing undergraduate degree at Atma Jaya Yogyakarta University. The Community Service Program is held at Hargosari Village, Tanjungsari District, Gunung Kidul Regency, Yogyakarta Special Region. The stages of the service are the law on the village basic services and infrastructure, as well as the village potential. After that, the teams will make the potential design the village. Identification of village potential using Strength, Weaknesses, Opportunities, Threats (SWOT) analysis. Furthermore, the teams design the program, for the design the village support program, namely the processing of corncobs into decorative lamps. The results of Haargosari has various potentials as well as processed product of corn and bamboo. In its implementation, it is necessary to establish an institution that is responsible for all tourism in Hargosari Village. Currentl, Hargosari Village has not fulfilled the formation of tourism village therefore it is necessaar to make the village potential development plan such as attractions, accessibility, amenities, activities, human resource, institution, and marketing, the Hargosari Village which becomes as one of the corn producing villages, has the opportunity to process corn cobs into decorative lamps that have high selling power.